P1483 Noninvasive multimodality imaging in diagnosis and management of cardiac sarcoidosis (CS). (17th January 2020) - Breskvar, U; Zupan Meznar, A; Kajdic, N; Antolic, B; Zizek, D
Abstract: Introduction: The clinical presentation of cardiac sarcoidosis (CS) ranges from an incidentally discovered condition to heart failure with risk of sudden cardiac death (SCD). As there is no single reliable test for detecting CS, noninvasive multimodality imaging plays a crucial role in establishing the diagnosis and SCD risk-stratification. We present a case of a young patient diagnosed with CS in whom, on the basis of multiple imaging results, dual-chamber ICD for primary prevention was implanted outside practice guidelines. Case: A 37-year-old woman was admitted to our hospital due to occasional palpitations and incidentally recorded nonsustained monomorphic ventricular tachycardia (VT). One year ago she was diagnosed with pulmonary sarcoidosis and was put on methylprednisolone; ECG, 24-h Holter monitoring and echocardiogram were normal. In the present admission control echocardiogram, with the exception of decreased longitudinal deformation of the basal and mid segments of the infero- and anterolateral left ventricle (LV) wall, was unremarkable. However, cardiac magnetic resonance (CMR) showed sub-epicardial late gadolinium enhancement (LGE) along the lower third of the antero- and inferolateral LV free wall and in the apical lateral segment of LV. Apart from some focal metabolically active lesions in the lungs and liver, fluorodeoxyglucose positron emission tomography with computed tomography (FDG PET/CT) displayed increased metabolic activity in the apical half of the antero- and infero-lateral segments of the LV. On the basis of this results CS was confirmed. Given the age, reduced longitudinal strain, notable LV LGE presence and increased cardiac metabolic activity, dual-chamber ICD to prevent SCD and possible bradycardia risk was implanted. The patient continued with immunosupressive therapy; 8 mg of methylprednisolone every other day. Conclusion: In our case, integrated multimodality imaging played a crucial role in establishing CS diagnosis and SCD risk stratification. A comprehensive evaluation of patients with CS is vital for making the best clinical decisions.